A study of the correlation of serum vitamin D levels to Child-Pugh and MELD-Na scoring system in cirrhosis of the liver - Patel, Jitendra Kumar; Mahur, Hemant Kumar; Jat, Shaitan Singh; Singh, D. P. (International Journal of Research in Medical Sciences, 2020)
Background: Vitamin D is a hormone with known effect on calcium homeostasis, but recently there is increasing recognition that it also is involved in cell proliferation and differentiation, has immunomodulatory and anti-inflammatory properties. These effect may explain its importance in the liver diseases. Vitamin D deficiency has been reported highly prevalent in Chronic liver disease (CLD) and there is an emerging interest to explore the relationship of vitamin D deficiency and severity of CLD. The aim of the study was to evaluate the correlation of serum vitamin D levels to the Child Pugh and MELD-Na scoring system in liver cirrhosis and to establish its relationship with the severity of the disease. Methods: Serum vitamin D levels were measured in 100 patients of CLD and 100 healthy controls. The degree of liver dysfunction was estimated by Child-Pugh and MELD-Na scores. Results: 91% of the CLD patients had subnormal vitamin-D levels. The mean vitamin D level in CLD patients was lower (15.97±7.45) than controls (30.12±6.60) with statistical significance (p= 0.0001). On linear regression vitamin D level showed significant negative correlation with Child Pugh score (r= –0.446, p<0.001) and MELD score (r= –0.395, p<0.001). Low vitamin D level was associated with poor outcome (mean vitamin D level 9.61±3.01 who died versus 16.52±7.47 who survived and discharged). Conclusions: CLD is associated with a significantly low level of vitamin D. The lower level of vitamin D is associated with severity of CLD, mortality and increased risk for complications. Awareness of serum vitamin D level in CLD patients is important to improve outcome.